2022
DOI: 10.3390/foods11213376
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic Analysis of Physicochemical Properties and Polysaccharide Composition during the Pile-Fermentation of Post-Fermented Tea

Abstract: Ultra-high performance liquid chromatography-quadrupole-time of flight tandem mass spectrometry (UHPLC-Q-TOF-MS/MS) was used to study the diversity of tea polysaccharides and the dynamic changes in the physicochemical indexes of tea samples. FT-IR spectra and the free radical scavenging ability of tea polysaccharides, during pile-fermentation of post-fermented tea, were analyzed. The results showed that 23 saccharide components in tea polysaccharides were identified: these belonged to 11 monosaccharides, 5 oli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 35 publications
0
8
0
Order By: Relevance
“…Glucoamylase activity was determined using dinitrosalicylic acid method, with glucose serving as the standard curve 6 . The sodium hydroxymethylcellulose method 7 and p ‐nitrophenol method 8 were used to ascertain cellulase and lipase activities respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Glucoamylase activity was determined using dinitrosalicylic acid method, with glucose serving as the standard curve 6 . The sodium hydroxymethylcellulose method 7 and p ‐nitrophenol method 8 were used to ascertain cellulase and lipase activities respectively.…”
Section: Methodsmentioning
confidence: 99%
“…Thermophilic strains can produce cellulase and amylase to increase the content of soluble sugar. 58,59 Among them, cellulase can degrade cellulose to produce glucose, and amylase can hydrolyze starch to produce oligosaccharides. Yeast can secrete enzymes that degrade phenol and produce a sweet xylitol substance.…”
Section: Flavonoids and Theirmentioning
confidence: 99%
“…Qingzhuan tea polysaccharides are acid polysaccharide or acidic glycoprotein binding to protein, mainly composed of arabinose, rhamnose, ribose, fucose, galactose, glucose, xylose, mannose, and galacturonic acid. , During the process of fermentation, the tea polysaccharides showed a trend of first rising and then decreasing due to the change in microbial population. Thermophilic strains can produce cellulase and amylase to increase the content of soluble sugar. , Among them, cellulase can degrade cellulose to produce glucose, and amylase can hydrolyze starch to produce oligosaccharides. Yeast can secrete enzymes that degrade phenol and produce a sweet xylitol substance .…”
Section: Chemical Ingredients and Their Composition Of Qztmentioning
confidence: 99%
“…Fermentation increased TPS in Liupao tea in consistency with the findings of other studies. 5,47 The cell wall polysaccharide structure analysis mentioned above found that the cellulose crystal structure was destroyed after fermentation, HC was degraded, and pectin was depolymerized to a certain extent. The carbohydrate correlation analysis during fermentation (Supporting Information, Figure S4) also proved that HC was significantly negatively correlated with TPS, and WSP was significantly positively correlated with TPS, indicating that the increase in TPS content may be due to the degradation of HC and the increase in WSP caused by the destruction of the cell wall structure.…”
Section: Journal Of Agricultural Andmentioning
confidence: 99%